Bacteriophage-mediated Glucosylation Can Modify Lipopolysaccharide O-Antigens Synthesized by an ATP-binding Cassette (ABC) Transporter-dependent Assembly Mechanism - Mann, Evan (J Biol Chem, 2015)
Lysogenic bacteriophages may encode enzymes that modify the structures of lipopolysaccharide O-antigen glycans, altering the structure of the bacteriophage receptor and resulting in serotype conversion. This can enhance virulence and has implications for antigenic diversity and vaccine development. Side chain glucosylation is a common modification strategy found in a number of bacterial species. To date, glucosylation has only been observed in O-antigens synthesized by Wzy-dependent pathways, one of the two most prevalent O-antigen synthesis systems. Here we exploited a heterologous system to study the glucosylation potential of a model O-antigen produced in an ATP-binding cassette (ABC) transporter-dependent system. Although O-antigen production is cryptic in Escherichia coli K-12, because of a mutation in the synthesis genes, it possesses a prophage glucosylation cluster, which modifies the GlcNAc residue in an α-l-Rha-(1→3)-d-GlcNAc motif found in the original O16 antigen. Raoultella terrigena ATCC 33257 produces an O-antigen possessing the same disaccharide motif, but its assembly uses an ABC transporter-dependent system. E. coli harboring the R. terrigena O-antigen biosynthesis genes produced an O-antigen displaying reduced reactivity toward antisera raised against the native R. terrigena repeat structure, indicative of an altered chemical structure. Structural determination using NMR revealed the addition of glucose side chains to the repeat units. O-antigen modification was dependent on a functional ABC transporter, consistent with modification in the periplasm, and was eliminated by deletion of the glucosylation genes from the E. coli chromosome, restoring native level antisera sensitivity and structure. There are therefore no intrinsic mechanistic barriers for bacteriophage-mediated O-antigen glucosylation in ABC transporter-dependent pathways.